Ethnic disparities and lifestyle determinants in the prevalence of cardiovascular disease among Han majority and Ha Ni ethnic minority older adults in rural Southwest China - You Huang; Qin Li; Mei Zuo; Lan Liu; Guo-Hui Li; Le Cai (BMC Cardiovascular Disorders)
Abstract Objectives Cardiovascular disease (CVD) is the leading cause of death in China. This study compared ethnic disparities and lifestyle determinants in the prevalence of CVD (hypertension, coronary heart disease [CHD], and stroke) among older adults of the Han majority and Ha Ni ethnic minority in rural southwest China, to provide evidence for preventing and controlling CVD among older-adult minority communities. Methods A multi-stage stratified random sampling method was used to select 1,413 Han majority participants and 1,402 Ha Ni ethnic minority participants aged ≥ 60 years in rural Southwest China. Data on general demographic characteristics, behavioral lifestyle, and self-reported diagnostic information for patients with CHD and stroke were collected using a standardized questionnaire. The height, weight, waist circumference, and blood pressure of each participant were recorded. The relationship between lifestyle factors and CVD was analyzed using multivariate logistic regression. Results Han majority older adults had a higher prevalence of CHD (6.4% vs. 3.6%) and stroke (7.9% vs. 2.9%) than their Ha Ni minority counterparts (P < 0.01). Han majority participants had a markedly higher prevalence of obesity, central obesity, and physical inactivity than their Ha Ni ethnic minority counterparts (9.2%, 48.3%, and 55.1% vs. 3.4%, 19.1%, and 49.2%, respectively, P < 0.01). By contrast, Ha Ni ethnic minority participants had a higher prevalence of current drinking than Han majority participants (31.2% vs. 14.4%, P < 0.01). Among Han majority and Ha Ni ethnic minority older adults, participants with central obesity (OR = 2.09, 95% CI: 1.62–2.69 vs. OR = 2.66, 95% CI: 1.88–3.76) had a higher risk of hypertension, participants with obesity (OR = 1.99, 95% CI: 1.02–3.67 vs. OR = 3.66, 95% CI: 1.39–9.66) were more likely to suffer from CHD, and participants with physical inactivity (OR = 1.88, 95% CI: 1.18–2.98 vs. OR = 2.29, 95% CI: 1.13–4.64) had a higher probability of suffering from stroke. Furthermore, Current drinking status increased the risk of CHD (OR = 2.31, 95% CI: 1.05–5.08), but decreased the risk of stroke (OR = 0.33, 95% CI: 0.13–0.83) in Ha Ni ethnic minority participants. Conclusion CHD and stroke are more prevalent among the Han majority older adults in rural Southwest China, and lifestyle factors significantly influence CVD.